Actor Analysis in Strategic Researches: Iraqi Kurdistan Case Study - ali akbar asadi (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2020)
The present article seeks to explain the Iraqi Kurdistan independence from the perspective of the interests and strategy of the effective actors, and utilizes the Actor Analysis Approach and MACTOR method. In this regard the main question is: what is the main convergences between interests and strategies of the main actors in Iraqi Kurdistan, and this circumstances how affects Kurdish independence? MACTOR method explicitly analyzes the relationships between actors and evaluates the relationships between actors and strategies. The main actors and strategies - including 11 main actors and 14 key strategies- were identified and then graphs were analyzed. The most important results regarding the Kurdistan independence are: the most influential actors in the subject; the actors competitiveness in the Kurdish independence; the most sensitive strategies; and the degree of convergence and divergence of actors regarding the strategies under consideration. The important result is that the sensitivity of the key actors and their relative consensus to disagree about establishment of Kurdish state and disintegration of Iraq and also concerns about creation of great Kurdistan state and as a result Increasing instability and Insecurity in the region, means that there are serious obstacles to ahead of Iraqi Kurds.